PEMBATALAN PERJANJIAN BANGUN GUNA SERAH (BUILD OPERATE TRANSFER/BOT) ANTARA PEMERINTAH DAERAH KOTA BOGOR DENGAN PIHAK SWASTA (PT PANCAKARYA GRAHATAMA INDONESIA) DITINJAU DARI SUDUT KITAB UNDANG-UNDANG HUKUM PERDATA - Lorenzo Marco; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2018)
The BOT (Build Operate Transfer) Agreement between Bogor Municipal Government and PT Pancakarya Grahatama Indonesia is an agreement to optimize Baranangsiang terminal assets as stated in the agreement Number: 601 / Perj.418-BPKAD / 2012 / Number: 005 / PGI / DIR / VI / 2012 . Until now, the agreement of both parties has not been able to be considered because of the change of authority of the terminal which formerly the authority of the City Government of Bogor to switch to the Central Government, resulting problems Whether the Government / Mayor Bogor can cancel the unilateral agreement BOT in the construction of Terminal Baranangsiang viewed from the point Civil Code? The research method used is normative legal research method supported by interview and field data. Based on the analysis that the BOT agreement between Bogor City Government and PT Pancakarya Grahatama is a valid and binding agreement between both parties and can not be canceled unilaterally by Bogor City Government, although there are new regulations that change the authority of terminal A Baranangsiang become the authority of Central Government . The Agreement may be canceled if it violates Article 1320 of the Criminal Code or violates the subjective and objective terms of the validity of the agreement. When the agreement is mutually agreed upon by both parties, the agreement must continue and act as a binding law as regulated in Article 1338 of the Criminal Code. Bogor City Government should immediately provide certainty to the PT Pancakarya Grahatama Indonesia for Baranangsiang terminal revitalization project can be immediately realized and need a revision (adedendum) agreement between the Government of Bogor City with PT Pancakarya Grahatama Indonesia related to changes in authority of terminal A Baranangsiang between PT. PGI with the Central Government.